Efficiency of application of different DNA probes in identifying marker chromosomes - Tavokina, L.V.; Brovko, A.O.; Baronova, E.V.; Moskalenko, E.P.; Gorovenko, N.G. (Вiopolymers and Cell, 2016)
The presence of marker chromosomes in the human karyotype always requires a special diagnostic approach. Determination of the marker chromosome type and structure is of great diagnostic and prognostic importance. There are several methods of marker chromosomes identification, which differ in their informative value. The paper presents the results of cytogenetic and FISH diagnostics of supernumerical marker chromosomes (SMC) cases in patients’ karyotype. Aim. To analyze the results of the cytogenetic and molecular cytogenetic diagnostics for patients with marker chromosomes, and to evaluate and compare the efficiency of the methods used. Methods. Karyotyping was done according to the standard methods. GTG, CBG, QFQ and NOR-Ag methods of differential staining were used. FISH was performed according to the manufacturer’s instructions for CEP, LSI and WCP DNA-probes. Results. Marker chromosome was found in 15 of 7989 patients. Application of standard staining methods was effective in 66.6 % of cases. Combination of differential staining and FISH allowed identifying a marker chromosome in 83.3 %. 90 % of all marker chromosomes were identified as isochromosomes and 60 % of them were derivative from chromosome 15. Conclusions. The use of WCP probes is a main step in the marker chromosome identification with further application of CEP/LSI probes. If a marker chromosome has nonspecific DNA sequences more sensitive methods should be use. Наявність маркерних хромосом в каріотипі людини завжди вимагає особливого діагностичного підходу. Визначення типу і структури маркерної хромосоми має велике діагностичне і прогностичне значення. Існує кілька методів ідентифікації маркерних хромосом, але різні методи мають різний рівень інформативності. В роботі наведені результати цитогенетичної та FISH діагностики випадків із надчисельними маркерними хромосомами в каріотипі пацієнтів. Мета. Аналіз результатів цитогенетичних і молекулярно-цитогенетичних досліджень каріотипів пацієнтів з маркерними хромосомами, а також оцінка і порівняння ефективності використаних методів. Методи. Каріотипування було виконано у відповідності до стандартних методів. Були використані GTG, CBG, QFQ і NOR-Ag методи диференціального фарбування. FISH була виконана відповідно до інструкцій виробника для CEP, LSI та WCP ДНК-проб. Результати. Маркерна хромосома була виявлена у 15 з 7989 пацієнтів. Застосування стандартних методів фарбування було ефективним у 66,6% випадків. Поєднання диференціального фарбування та FISH дозволило ідентифікувати маркерні хромосоми у 83,3 %. 90 % всіх маркерних хромосом були визначені як ізохромосоми і 60 % з них були похідними від хромосоми 15. Висновки. Використання WCP ДНК-проб є основним етапом ідентифікації маркерних хромосом з наступним застосуванням CEP та LSI ДНК-проб. Якщо маркерна хромосома має неспецифічні послідовності ДНК, то у таких випадках повинні бути застосовані більш чутливі методи. Наличие маркерных хромосом в кариотипе человека всегда требует особого диагностического подхода. Определение типа и структуры маркерной хромосомы имеет большое диагностическое и прогностическое значение. Существует несколько методов идентификации маркерных хромосом, но разные методы имеют разный уровень информативности. В работе приведены результаты цитогенетической и FISH диагностики случаев со сверхчисленными маркерными хромосомами в кариотипе пациентов. Цель. Анализ результатов цитогенетических и молекулярно-цитогенетических исследований кариотипов пациентов с маркерным хромосомами, а также оценка и сравнение эффективности использованных методов. Методы. Кариотипирование выполнено согласно стандартных методик. Использованы GTG, CBG, QFQ и NOR-Ag методы дифференциального окрашивания. FISH выполнена в соответствии с инструкциями производителя для CEP, LSI и WCP ДНК-проб. Результаты. Маркерная хромосома обнаружена у 15 из 7989 пациентов. Применение стандартных методов окрашивания было эффективным в 66,6 % случаев. Сочетание дифференциального окрашивания и FISH позволило идентифицировать маркерные хромосомы в 83,3 %. 90 % всех маркерных хромосом были определены как изохромосомы и 60 % из них были производными от хромосомы 15. Выводы. Использование WCP ДНК-проб является основным этапом идентификации маркерных хромосом с последующим применением CEP и LSI ДНК-проб. Если маркерная хромосома имеет неспецифические последовательности ДНК, то в таких случаях должны быть применены более чувствительные методы.